Analysis of Effect of Service Quality on Satisfaction Inpatient at Ibunda Hospital, Bagan Batu Village - Herdianto Herdianto; Dedi Afandi; Abdurrahman Hamid (Budapest International Research and Critics University, 2022)
This study aims to determine and analysis of effect of service quality on satisfaction inpatient at Ibunda Hospital, Bagan Batu Village. This study uses a quantitative approach. This research is conducted at Ibunda Hospital, Bagan Batu Village. The time of this research is from May to July 2022. The population in this study are inpatients at Ibunda Hospital. The technique of determining the informants used proportional sampling. The sample used is 96 respondents using the slovin sampling technique. The analytical method used in this study is a simple linear regression analysis method. The results show that service quality has a significant effect on satisfaction inpatient at Ibunda Hospital, Bagan Batu Village.